2002
DOI: 10.1007/s00216-002-1436-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of flavonoids in Ginkgo biloba L. and its phytopharmaceuticals by capillary electrophoresis with electrochemical detection

Abstract: A high-performance capillary electrophoretic (CE) method with electrochemical detection (ED) has been developed for determination of the pharmacologically active flavonoids in Ginkgo biloba L. and phytopharmaceuticals containing its extract. Epicatechin, catechin, rutin, apigenin, luteolin, and quercetin are important flavonoids in this plant. Operated in a wall-jet configuration, a 300 micro m diameter carbon-disk electrode was used as working electrode with good response to the six analytes at +1000 mV (rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 12 publications
3
31
0
Order By: Relevance
“…The above findings showed that UV-B irradiation could be applied to stimulate the production of secondary metabolite compounds in nature product. Most recently, Ginkgo flavonoids attracted much attention for their antimicrobial, neuroprotector, anti-mutational, improved cardiovascular well-being, and anticancer activity (Cao, Chu, Fang, & Ye, 2002;Ding et al, 2009). Hence, it is of key interest to enhance the productivities of total flavonoids in Ginkgo leaves applying biotechnology method such as abiotic elicitors of cell engineering (Xu, Dong, Wang, & Huang, 2009).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 98%
“…The above findings showed that UV-B irradiation could be applied to stimulate the production of secondary metabolite compounds in nature product. Most recently, Ginkgo flavonoids attracted much attention for their antimicrobial, neuroprotector, anti-mutational, improved cardiovascular well-being, and anticancer activity (Cao, Chu, Fang, & Ye, 2002;Ding et al, 2009). Hence, it is of key interest to enhance the productivities of total flavonoids in Ginkgo leaves applying biotechnology method such as abiotic elicitors of cell engineering (Xu, Dong, Wang, & Huang, 2009).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 98%
“…Ginkgo biloba is a common medicinal plant in China and the secondary metabolites of ginkgo, flavonoids and ginkgolides, are excellent drugs used in the treatment of peripheral arterial diseases, tinnitus, neurological disorders, sclerosis of cerebral arteries, and cerebral ageing (Cao et al 2002). As a therapeutic drug, it has no side effects even after long periods of use, and phytopharmaceuticals made from G. biloba are readily accessible throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…Genistein (4', 5, 7-trihydroxyisoflavone) is a widely distributed isoflavone primarily present in soy, Ginkgo biloba extract, oregano and sage [55,56]. It was first isolated from soybean in 1931 [57].…”
Section: Genisteinmentioning
confidence: 99%